Bat aggregational response to pest caterpillar emergence - Ján Blažek (Nature Portfolio, 2021)
Abstract Moths (Lepidoptera) are major agricultural and forest pests in many parts of the world, including Europe, with many causing great economic damage to crops, horticultural plants, stored items, and wool products. Here, we focus on two ecologically similar inchworms, Operophtera brumata and Erannis defoliaria, known for their high foliage consumption during the spring emergence of caterpillars. We hypothesise that bats could play a role in reducing pests such as caterpillars by switching to this abundant emerging prey. At two infested and one control forest sites, caterpillars were sampled during spring to determine levels of infestation. At the same time, bat flight activity was monitored during the peak in caterpillar abundance. During the spring caterpillar outbreak, we collected faecal samples of forest-dwelling bats capable of using gleaning. The majority of samples were positive for our focus species, being 51.85% for O. brumata and 29.63% for E. defoliaria faecal samples. The foraging activity of two gleaning bats, Myotis nattereri and Myotis bechsteinii, increased at both infested sites, but not at the control site, during caterpillar emergence, as did foraging of Plecotus auritus/austriacus, which used both gleaning and aerial hawking. We conclude that both specialists and occasional gleaners, which prefer different prey but are able to switch their foraging strategies, aggregate at sites during pest emergence and, as such, our results confirm the high potential of bats to reduce numbers of pest species such as caterpillars.